A study on the factors influencing young generation's registration as voters / Audrey Laurentius and Harold Alta Julain - Laurentius, Audrey; Julain, Harold Alta (2012)
The aim of this research was to examine the factors influencing young generation’s registration as voters among the students in Samarahan. 150 questionnaires were distributed randomly to students of three main campuses in Samarahan, which is Universiti Teknologi Mara Samarahan campus (UiTMKS), Universiti Malaysia Sarawak (UNIMAS), and Maktab Perguruan Tun Abdul Razak (MPTAR). The Statistic Package for Social Science (SPSS) was used to analyze the results obtained from the questionnaires that have been collected. The results of this study indicated that the most factors that influence young generation’s registration to become voters was due to the involvement of too many political parties in one election, that it created confusion among the students in becoming a voter. It is clear from the present study that young generations in Samarahan wanted the voter registration process to be implemented in the Internet as it is an easy and convenient way for them to register.